Isolation, Detection and Analysis of Circulating Tumour Cells: A Nanotechnological Bioscope - Upama Das; Soumyabrata Banik; Sharmila Sajankila Nadumane; Shweta Chakrabarti; Dharshini Gopal; Shama Prasada Kabekkodu; Pornsak Srisungsitthisunti; Nirmal Mazumder; Rajib Biswas (MDPI AG, 2023)
Cancer is one of the dreaded diseases to which a sizeable proportion of the population succumbs every year. Despite the tremendous growth of the health sector, spanning diagnostics to treatment, early diagnosis is still in its infancy. In this regard, circulating tumour cells (CTCs) have of late grabbed the attention of researchers in the detection of metastasis and there has been a huge surge in the surrounding research activities. Acting as a biomarker, CTCs prove beneficial in a variety of aspects. Nanomaterial-based strategies have been devised to have a tremendous impact on the early and rapid examination of tumor cells. This review provides a panoramic overview of the different nanotechnological methodologies employed along with the pharmaceutical purview of cancer. Initiating from fundamentals, the recent nanotechnological developments toward the detection, isolation, and analysis of CTCs are comprehensively delineated. The review also includes state-of-the-art implementations of nanotechnological advances in the enumeration of CTCs, along with future challenges and recommendations thereof.